Comparative anti-tumor efficacy of two orally administered platinum(IV) drugs in nude mice bearing human tumor xenografts - Sova, Petr; Mistr, Adolf; Kroutil, Aleš; Žák, František; Poučková, Pavla; Zadinová, Marie (Anticancer Drugs, 2006)
The oral anti-tumor activity of a novel platinum(IV) complex, coded as LA-12, with a bulky adamantylamine ligand was evaluated and compared with another platinum(IV) complex satraplatin. The human carcinoma xenografts of colon HCT116, prostate PC3, and ovarian A2780 and A2780/cisR (resistant to cisplatin) were used to evaluate the in-vivo anti-tumor activity. The daily x 5 repeated dose regimen in equimolar doses of LA-12 and satraplatin, administered in 2 cycles, was selected for this evaluation. All doses of LA-12 and satraplatin were significantly effective in comparison with the control. The activities of LA-12 in all doses and all used tumor xenografts were higher than equimolar doses of satraplatin. The highest effect was reached with LA-12 at a dose of 60 mg/kg. The shapes of growth curves of ovarian carcinoma A2780 and its subline resistant to cisplatin after therapy with LA-12 were very similar. This shows that LA-12 is able to overcome resistance to cisplatin.
Keywords: cisplatina; Cisplatin; transplantace heterologní; nádorové buněčné linie; Antineoplastic Agents; Mice; zvířata; Colonic Neoplasms; chemorezistence; nádory vaječníků; Financing, Organized; protinádorové látky; financování organizované; myši nahé; mužské pohlaví; amantadin; Ligands; Amantadine; nádory prostaty; Cell Survival; viabilita buněk; Transplantation, Heterologous; Drug Resistance, Neoplasm; Prostatic Neoplasms; ligandy; Mice, Nude; myši; nádory tračníku; ženské pohlaví; Organoplatinum Compounds; Animals; Ovarian Neoplasms; organoplatinové sloučeniny; Male; Cell Line, Tumor; Female